2015
DOI: 10.3892/etm.2015.2518
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-rich saline promotes motor functional recovery following peripheral nerve autografting in rats

Abstract: Despite the application of nerve grafts and considerable microsurgical innovations, the functional recovery across a long peripheral nerve gap is generally partial and unsatisfactory. Thus, additional strategies are required to improve nerve regeneration across long nerve gaps. Hydrogen possesses antioxidant and anti-apoptotic properties, which could be neuroprotective in the treatment of peripheral nerve injury; however, such a possibility has not been experimentally tested . The aim of the present study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…For example, it has been reported previously that HS injection prevents cognitive deficits in animal models following traumatic brain injury, effects which were proposed to involve antioxidant activity and activation of BDNF-related synaptic plasticity [16]. HS has also been shown to alleviate peripheral nerve injury and promote functional recovery after sciatic nerve autografting in rats [17]. Moreover, hydrogen-rich water prevents the development and progression of depressive-like behavior in rats, through its capacity to inhibit inflammasome activation [18].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported previously that HS injection prevents cognitive deficits in animal models following traumatic brain injury, effects which were proposed to involve antioxidant activity and activation of BDNF-related synaptic plasticity [16]. HS has also been shown to alleviate peripheral nerve injury and promote functional recovery after sciatic nerve autografting in rats [17]. Moreover, hydrogen-rich water prevents the development and progression of depressive-like behavior in rats, through its capacity to inhibit inflammasome activation [18].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies in recent years have found that molecular hydrogen can reduce the production of inflammatory factors 28,38,39 and increase the release of anti-inflammatory factors, thereby playing an anti-inflammatory role. Hydrogen gas also has anti-apoptotic effects 32,40,41 and affects the hormone levels and activity. 42,43 Based on the above research, we found that the formation of chronic nasal mucosal inflammation is closely related to oxidative stress mechanisms.…”
Section: Therapeutic Mechanism Of Hydrogenmentioning
confidence: 99%